2021
DOI: 10.1186/s12943-021-01411-w
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated exosomes promote lung cancer metastasis through multiple mechanisms

Abstract: As an important medium of intercellular communication, exosomes play an important role in information transmission between tumor cells and their microenvironment. Tumor metastasis is a serious influencing factor for poor treatment effect and shortened survival. Lung cancer is a major malignant tumor that seriously threatens human health. The study of the underlying mechanisms of exosomes in tumor genesis and development may provide new ideas for early and effective diagnosis and treatment of lung cancer metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 73 publications
(71 reference statements)
2
64
0
Order By: Relevance
“…The results of numerous studies indicate that EVs contribute to the malignant phenotype and the survival of primary tumor cells, regulating the processes of proliferation and apoptosis [ 33 , 34 ]. EVs also participate in tumor spread by enhancing the migratory and invasive activity of cancer cells and stimulation of angiogenesis [ 35 , 36 , 37 , 38 ]. In addition, EVs secreted by tumor cells are involved in the processes of the tumor–stroma interaction, reorganization of tissue microenvironment, pre-metastatic niche formation, and reprogramming of immune cells to evade anti-tumor immunity [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of numerous studies indicate that EVs contribute to the malignant phenotype and the survival of primary tumor cells, regulating the processes of proliferation and apoptosis [ 33 , 34 ]. EVs also participate in tumor spread by enhancing the migratory and invasive activity of cancer cells and stimulation of angiogenesis [ 35 , 36 , 37 , 38 ]. In addition, EVs secreted by tumor cells are involved in the processes of the tumor–stroma interaction, reorganization of tissue microenvironment, pre-metastatic niche formation, and reprogramming of immune cells to evade anti-tumor immunity [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer has developed into one of the most common malignant tumors in the world, with the highest incidence and mortality rate ( Jiang et al, 2021a ; Drusbosky et al, 2021 ). The incidence of lung cancer has been on the rise due to factors such as smoking and environmental pollution ( Koch et al, 2021 ; Raguraman et al, 2021 ).…”
Section: Sers Technology For Exosome Detectionmentioning
confidence: 99%
“…Nowadays, more and more studies have shown that exosomes play important roles in organisms, such as cell-to-cell communication ( Ruhland et al, 2020 ; Schneider et al, 2021 ), immune response ( Kalluri and LeBleu, 2020 ; Su et al, 2020 ), cell growth and differentiation ( Yin et al, 2021 ; Zarnowski et al, 2021 ), as well as molecular transport ( Zhu Q. et al, 2021 ). Crucially, the concentration and phenotype of exosomes have been proved to reflect the state of their parental cells and associate with the occurrence and development of various diseases, such as cancers ( Jiang et al, 2021 ), infectious diseases ( Ning et al, 2021 ; Xie et al, 2021 ), metabolic, and cardiovascular diseases ( Kalluri and LeBleu, 2020 ). Therefore, developing exosome isolation methods with high efficiency and selectivity will definitely promote the deep understanding of the functions of exosome, as well as the accurate diagnosis and treatment of diseases.…”
Section: Introductionmentioning
confidence: 99%